Most frequent dermatoses at a vulvar pathology outpatient clinic - Gabriella Cerazi Sartori; Rafaela Tricca Wicher; Flávia Regina Ferreira; Valéria Holmo Batista (Anais Brasileiros de Dermatologia, 2018)
Abstract: The vulva corresponds to the external female genitalia. Special features of this region favor a wide range of diseases, whose knowledge allows for better clinical management, impacting on the quality of life. This is a cross-sectional and descriptive study carried out at a vulvar pathology outpatient clinic, between May and December/ 2015. Data obtained from a standard form included demographic parameters, habits, and vulvar dermatosis and allowed to identify the epidemiological profile of patients with vulvar dermatosis treated in this outpatient clinic and to determine the most prevalent dermatoses. Our results, partially concordant with the literature, provide original data that should stimulate further studies